Memory Extension Techniques for Mini-Computers - Poppendieck, Mary; Desautels, Edouard (University of Wisconsin-Madison Department of Computer Sciences, 1976)
The address range of mini-computers purchased two to three years ago was typically 32K words. Many owners of these computers are realizing that this is no longer adequate for their application. Various methods of extending the memory of mini-computers are becoming available. This paper discusses and compares the various methods of addressing more memory which are becoming available for mini-computers.